HIJAB CONSTRUCTION ON SOCIAL MEDIA IN THE FASHION INDUSTRY IN INDONESIA - Dedek Pradesa; Mailin Mailin; Ahmad Sofian; Rizka Gusti Anggraini (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2022)
The proliferation of trends and hijab phenomena has not escaped the media role, as the media has hada major impact on society. The popularity of media - induced hijab has made the hijab a new item in the business world too. The paper focuses on debasing and discussing the construction of hijab in social media in the Indonesian fashion industry. As the development of the Pict (information communication technology), which expresses virtual public space, we also presented new targets in the Muslim fashion business in Indonesia. Industrialization of fashion hijab is not without the influence of capitalism. The dominance and rejuvenation of capitalist power has penetrated into the realm of religion, as well as into the cultural industrial products that have become a symbol and accessory of noble appearance.